Silvicultural and its practise in Malaysia / Mohd Lokman Che Jusoh - Che Jusoh, Mohd Lokman (2004)
Silviculture is the art and science of tree production. It is based on an understanding of silvics, which is the study of forests and forest relationships. Silviculture is practiced on the assumption that a forest environment can be manipulated to make it more favourable to the growth of trees than the natural environment. Silviculture are been divided into two system and the application of this system are depend on the condition of the forest. In Malaysia, silviculture are been introduce when forest management are been modernize in 1930. There been a lot of modified to the usual silviculture system and the system are been replace according to the suitability to the forest. Silviculture are been applied in forest management system in Malaysia. Beginning with Malayan Improvement felling in 1910 to 1932 and then follow by Malayan Refined Improvement Felling (1933 - 1949). After that it's been replace with Malayan Uniform System in 1949 and today Selective Management System was used beginning at 1971. Silviculture is very important in forest management because it give a lot of benefit that can improve quality of production and also give benefit to nature.